2018
DOI: 10.1109/tie.2017.2748033
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Compensation of Charge Trapping Induced by Ionizing Radiation in MOS Capacitors

Abstract: Abstract-The objective of this work is to explore the capability of a charge trapping control loop to continuously compensate charge induced by ionizing radiation in the dielectric of MOS capacitors. To this effect, two devices made with silicon oxide have been simultaneously irradiated with gamma radiation: one with constant voltage bias, and the other working under a dielectric charge control. The experiment shows substantial charge trapping in the uncontrolled device whereas, at the same time, the control l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The voltage shift is an indirect inference to the changes in the net charge trapped in the dielectric. This is compatible with the observations in [27], which indicated that charge injection changed when the net charge levels around which they were studied were far apart one of the other. In practice, this means that constant multi-exponential charge models are valid for MOS capacitors, so long as the total displacement of the net charge is not significantly changed.…”
Section: A Building the Dr Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…The voltage shift is an indirect inference to the changes in the net charge trapped in the dielectric. This is compatible with the observations in [27], which indicated that charge injection changed when the net charge levels around which they were studied were far apart one of the other. In practice, this means that constant multi-exponential charge models are valid for MOS capacitors, so long as the total displacement of the net charge is not significantly changed.…”
Section: A Building the Dr Modelsupporting
confidence: 90%
“…To mitigate this problem, extensive design and shielding strategies are routinely implemented. Besides, compensation of charge trapped in SiO 2 MOS capacitors induced by gamma radiation using sigma-delta controls has been demonstrated recently in [27]. Ionizing radiation such as gamma and Xray radiation can be understood as an external disturbance in a sliding mode controller affecting the net charge in the dielectric [28].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the interesting recovery behavior after about 2.4 krad (9.3 minutes at the dose rate of 256 rad/min) is a result of the 1.7 MHz switching frequency of the regulator design. Rapidly changing bias conditions have been shown to improve recombination rates [28]. At the 14 krad point of failure, once the output voltage has dropped to 1.3 V it is feasible a localized net-gain of e/h recombination could form as a result of the lower bias.…”
Section: Experimental Results: Switching Regulatorsmentioning
confidence: 99%
“…One possible explanation for the interesting recovery behavior after about 2.4 krad (9.3 minutes at the dose rate of 256 rad/min) is a result of the 1.7 MHz switching frequency of the regulator design. Rapidly changing bias conditions have been shown to improve recombination rates [22]. At the 14 krad point of failure, once the output voltage has dropped to 1.3 V it is feasible a localized net-gain of e/h recombination could form as a result of the lower bias.…”
Section: Experimental Results: Switching Regulatorsmentioning
confidence: 99%